Dual-wavelength hybrid optoacoustic-ultrasound biomicroscopy for functional imaging of large-scale cerebral vascular networks - Rebling, Johannes; Estrada, Hector; Gottschalk, Sven; Sela, Gali; Zwack, Michael; Wissmeyer, Georg; Ntziachristos, Vasilis; Razansky, Daniel (Journal of Biophotonics, 2018)
A critical link exists between pathological changes of cerebral vasculature and diseases affecting brain function. Microscopic techniques have played an indispensable role in the study of neurovascular anatomy and functions. Yet, investigations are often hindered by suboptimal trade-offs between the spatiotemporal resolution, field-of-view (FOV) and type of contrast offered by the existing optical microscopy techniques. We present a hybrid dual-wavelength optoacoustic (OA) biomicroscope capable of rapid transcranial visualization of large-scale cerebral vascular networks. The system offers 3-dimensional views of the morphology and oxygenation status of the cerebral vasculature with single capillary resolution and a FOV exceeding 6 × 8 mm2, thus covering the entire cortical vasculature in mice. The large-scale OA imaging capacity is complemented by simultaneously acquired pulse-echo ultrasound (US) biomicroscopy scans of the mouse skull. The new approach holds great potential to provide better insights into cerebrovascular function and facilitate efficient studies into neurological and vascular abnormalities of the brain.
CRIS-Team Scopus Importer:2023-03-08
Keywords: blood vessels; brain; cerebral; microscopy; photoacoustics; ultrasound